The Decameron (Day 1 to Day 5) : Containing an hundred pleasant Novels - Boccaccio, Giovanni, 1313-1375; Florio, John, 1553?-1625 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Decameron (Day 1 to Day 5)" by Giovanni Boccaccio is a collection of short stories written between 1348 and 1353. Ten young people flee plague-ridden Florence to shelter in a secluded villa, where they pass time by telling tales. Over ten nights, they share 100 stories ranging from erotic to tragic love, clever wit, practical jokes, and life lessons. The tales satirize clergy, explore human desires and ambitions, and reflect Italian society during the Black Death era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Decameron
Release date is 2016-07-22
Produced by Clare Graham and Marc D'Hooghe (Images generously made available by the Internet Archive.)
Keywords: Plague -- Europe -- History -- Fiction; Storytelling -- Fiction; Allegories; Frame stories